Mathematical Model for the Placement of Hydrogen Refueling Stations to Support Future Fuel Cell Trucks - Brenda Hernandez (IEEE, 2021)
Fuel cell- and electric-powered trucks are promising technologies for zero-emission heavy-duty transportation. Recently, Fuel Cell Trucks (FCT) have gained wider acceptance as the technology of choice for long-distance trips due to their lighter weight and shorter fueling time than electric-powered trucks. Broader adoption of Fuel Cell Trucks (FCT) requires planning strategies for locating future hydrogen refueling stations (HRS), especially for fleets that transport freight along intercity and inter-country highways. Existing mathematical models of HRS placement often focus on inner-city layouts, which make them inadequate when studying the intercity and intercountry FCT operation scale of FCT. Furthermore, the same models rarely consider decentralized hydrogen production from renewable energy sources, essential for decarbonizing the transportation sector. This paper proposes a mathematical model to guide the planning of the hydrogen infrastructure to support future long-haul FCTs. First, the model uses Geographic Information System (GIS) data to determine the HRS’s optimal number and location placement. Then, the model categorizes and compares potential hydrogen production sources, including off-site delivery and on-site solar-to-hydrogen production. The proposed model is illustrated through a case study of the west coastal area of the United States (from Baja California, Mexico to British Columbia, Canada). Different geospatial scenarios were tested, ranging from the current operational distance of FCEV (250km) and future releases of hydrogen FCT (up to 1,500km). Results highlight the capabilities of the model in identifying the number and location of the HRS based on operation distances, in addition to determining the optimal hydrogen production technology for each HRS. The findings also confirm the viability of green hydrogen production through solar energy, which could play a critical role in a low-carbon transportation future.